Comparative evaluation of the utility of two oral examination tools in assessing oral health in stroke patients with indwelling gastric tubes - Shuangyan Tu; Menglin Jiang; Rong Yang; Zhiqiang Deng; Cairong Zhu; Muke Zhou; Zhangyan Peng; Lihong Zhao (PLoS ONE, 2025)
Purpose To identify the scale that is more suitable for oral health assessment in stroke patient population with indwelling gastric tubes. Methods A total of 198 patients with indent gastric tubes were selected from 1250 stroke patients to evaluate their oral health using both the BOAS and the OHAT scales. The scores obtained from both scales were then compared to evaluate the feasibility, reliability, and validity of each scale in assessing oral health among stroke patients with indwelling gastric tubes. Results The results showed that both the BOAS and OHAT scales exhibited good reliability and validity in stroke patients with indwelling gastric tubes. The Cronbach’s alpha coefficients of BOAS and OHAT in stroke patients with indwelling gastric tubes were 0.89 and 0.91, respectively. In the exploratory factor analysis, one and two common factors were extracted from the two scales, with cumulative variance contributions of 65.89% and 71.85%, respectively. In addition, potential influencing factor correlation analysis found that gender and marital status had a significant correlation with the BOAS score(P < 0.05), the Activities of daily living (ADL) score was found to be significantly correlated with the OHAT score (P < 0.05). Drinking, smoking, income, consciousness, and the result of the water swallow test were all correlated with BOAS and OHAT scores(P < 0.01). Conclusions The BOAS and OHAT have demonstrated good reliability and validity and in their ability to assess the oral health of stroke patients with indwelling gastric tubes. Therefore, it is recommended that the selection of oral assessment scales should be further refined in different disease stages of stroke patients to assess the oral health status of patients more accurately and personalized.